Characterizing the Urban Growth from 1975 to 2003 of Hanoi City Using Remote Sensing and a Spatial Metric - Hai, Pham Minh; Yamaguchi, Yasushi (Universitas Muhammadiyah Surakarta, 2007)
This study explores an approach of combining remote sensing and a spatial metric to characterize land use change in Hanoi, Vietnam. The work is based on the land cover information of 4 different times derived from LandsatÂ and ASTER data from 1975 to 2003. This study adopted the spatial metrics; the percentage of like adjacency (PLADJ), which calculates the number of like adjacencies involving the focal class, divided by the focal number of cell adjacencies involving the focal class, multiplied by 100 to convert to a percentage. The result successfully showed proportions of the fragmented and the aggregated areas in urbanization for each development time. During the rapid urbanization periods in 1975 â 1984 and 1984 â 1992, a large proportion of the interior non developed and aggregated non developed was converted to developed landscape, whereas fragmented non developed to developed markedly happened in 2001 â 2003. The study provided intuitive description and separation of three urbanization patterns such as infill, expansion, and outlying. Quantitative assessment revealed that the proportion of the expansion and infill steadily increased, whereas the proportion of the outlying decreased in past 30 years. The combined approach using remote sensing and a spatial metric is an effective method to improve understanding of urbanization patterns and to provide visualization of spatial â temporal change due to urbanization.